A Genome-Wide Screen Reveals a Role for the HIR Histone Chaperone Complex in Preventing Mislocalization of Budding Yeast CENP-A. Issue 1 (16th July 2018) - Ciftci-Yilmaz, Sultan; Au, Wei-Chun; Mishra, Prashant K; Eisenstatt, Jessica R; Chang, Joy; Dawson, Anthony R; Zhu, Iris; Rahman, Mahfuzur; Bilke, Sven; Costanzo, Michael; Baryshnikova, Anastasia; Myers, Chad L; et al.
Abstract: Centromeric localization of the evolutionarily conserved centromere-specific histone H3 variant CENP-A (Cse4 in yeast) is essential for faithful chromosome segregation. Overexpression and mislocalization of CENP-A lead to chromosome segregation defects in yeast, flies, and human cells. Overexpression of CENP-A has been observed in human cancers; however, the molecular mechanisms preventing CENP-A mislocalization are not fully understood. Here, we used a genome-wide synthetic genetic array (SGA) to identify gene deletions that exhibit synthetic dosage lethality (SDL) when Cse4 is overexpressed. Deletion for genes encoding the replication-independent histone chaperone HIR complex ( HIR1, HIR2, HIR3, HPC2 ) and a Cse4 -specific E3 ubiquitin ligase, PSH1, showed highest SDL. We defined a role for Hir2 in proteolysis of Cse4 that prevents mislocalization of Cse4 to noncentromeric regions for genome stability. Hir2 interacts with Cse4   in vivo, and hir2 ∆ strains exhibit defects in Cse4 proteolysis and stabilization of chromatin-bound Cse4 . Mislocalization of Cse4 to noncentromeric regions with a preferential enrichment at promoter regions was observed in hir2 ∆ strains. We determined that Hir2 facilitates the interaction of Cse4 with Psh1, and that defects in Psh1 -mediated proteolysis contribute to increased Cse4 stability and mislocalization of Cse4 in the hir2 ∆ strain. In summary, our genome-wide screen provides insights into pathways that regulate proteolysis of Cse4 and defines a novel role for the HIR complex in preventing mislocalization of Cse4 by facilitating proteolysis of Cse4, thereby promoting genome stability.